Research on the influence of waterproof layer on lining mechanical performance under early temperature load - Mingshe Sun; Zhenxiang Guan; Caixia Guo; Xin Xi; Sen Tian (PLoS ONE, 2025)
The installation of waterproof layer in the composite lining will change the tangential constraint conditions on the initial support side of lining, affecting the lining mechanical performance under early temperature loads. Based on a loess double track railway tunnel, the influence of tangential constraints on lining mechanical performance under concrete hydration heat temperature load was studied by numerical simulation. Interactions between surrounding rock, initial support, waterproof layer and lining were taken into consideration in the simulation model. The influences of concrete initial pouring temperature, surface heat dissipation coefficient on thermal stress of lining were analyzed and engineering suggestions for preventing early crack were proposed as well. The results show that the greater tangential constraints imposed by the waterproof layer on lining, the greater lining thermal tensile stress, and the higher the risk of through crack. Lining springing constrained by inverted arch is prone to cracking and should be paid more attention in the construction process. Lining thermal stress is significantly affected by concrete initial pouring temperature, and appropriately reducing the pouring temperature is conducive to prevent the occurrence of early cracks. For waterless tunnels, the waterproof layer may be considered to be omitted, and the tangential constraints on the lining can be reduced by installing a thin polyethylene plastic film. The research results can be useful for the design of the composite lining structure.